Clinical assessment and prevalence of parkinsonism in Japanese elderly people. (3rd August 2015) - Nakashita, S.; Wada‐Isoe, K.; Uemura, Y.; Tanaka, K.; Yamamoto, M.; Yamawaki, M.; Nakashima, K.
Abstract : Background: Parkinsonism is often observed in the elderly. To clarify the prevalence of parkinsonism‐associated diseases and conditions, we conducted a population‐based study in a rural island town in western Japan, Ama‐cho. Methods: Participants included 924 subjects aged 65 years or older residing in the town. Between 2008 and 2011, participants were assessed via standardized neurological examination scales, and Brain MRIs were carried out in 2010. Based on the results of assessment using the modified Unified Parkinson's Disease Rating Scale and a standardized neurological examination, participants were diagnosed as having parkinsonism or mild parkinsonian signs (MPS), or as displaying normal motor conditions (M‐normal). Results: Of the 729 participants screened, 70 subjects were diagnosed as having parkinsonism, corresponding to a crude prevalence rate of 9.6% (95% CI, 7.9–11.3%), while 167 MPS subjects (22.9%) and 492 subjects experiencing M‐normal (67.5%) were observed. Parkinsonism was found in association with various diseases such as Vascular parkinsonism, Lewy body disease, Alzheimer's disease (AD), and idiopathic normal‐pressure hydrocephalus. Among the subjects with dementia, the proportion with parkinsonism was higher in the non‐AD dementia group. Conclusion(s): Parkinsonism occurs in association with several diseases in elderly people. Parkinsonism was also found to be commonly associated with cognitive impairment.